Advanced Active Power Filter Performance for Grid Integrated Hybrid Renewable Power Generation Systems - S. Guru Prasad; K S Srikanth; B V Rajanna (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
An active power filter implemented with a four leg voltage-source inverter using a predictive control scheme is presented. The use of a four leg voltage-source inverter allows the compensation of current harmonic components, as well as unbalanced current generated by single-phase nonlinear loads. A detailed yet simple mathematical model of the active power filter, including the effect of the equivalent power system impedance, is derived and used to design the predictive control algorithm. The compensation performance of the proposed active power filter and the associated control scheme under steady state and transient operating conditions is demonstrated through simulations and experimental results.